1981
DOI: 10.1093/oxfordjournals.aje.a113097
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Hypertension in a Community of Older Adults

Abstract: The relationship between diabetes and hypertension in 3456 residents of Rancho Bernardo, California, aged 50-79 years, surveyed in 1972-1974, was analyzed in depth in both the univariate mode and after adjustments for the potential confounding effects of age, obesity and diuretic medication. An association between diabetes and hypertension was present in both men and women at all ages, and the association was strongest for subjects having the best evidence for diabetes, i.e., both historical diabetes and fasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
38
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(43 citation statements)
references
References 0 publications
5
38
0
Order By: Relevance
“…In the Framingham study, systolic hypertension was ~1.5 times more prevalent in diabetic than in nondiabetic patients, with the risk being higher in women than in men (11,12). Several other studies, including the population survey conducted in Tecumseh, Michigan (13,14), and a series of elderly diabetic patients (aged 50-79 yr) reported by Barrett-Conner et al (15), have confirmed that the tendency to develop hypertension is more apparent among diabetic women than diabetic men. Note that all of the aforementioned studies have been conducted in predominantly Caucasian populations residing in industrialized areas of the United States and western Europe.…”
Section: Epidemiology and Prevalencementioning
confidence: 76%
“…In the Framingham study, systolic hypertension was ~1.5 times more prevalent in diabetic than in nondiabetic patients, with the risk being higher in women than in men (11,12). Several other studies, including the population survey conducted in Tecumseh, Michigan (13,14), and a series of elderly diabetic patients (aged 50-79 yr) reported by Barrett-Conner et al (15), have confirmed that the tendency to develop hypertension is more apparent among diabetic women than diabetic men. Note that all of the aforementioned studies have been conducted in predominantly Caucasian populations residing in industrialized areas of the United States and western Europe.…”
Section: Epidemiology and Prevalencementioning
confidence: 76%
“…Frequently, HT is associated with DM and its prevalence doubles in diabetics compared to the general population. 1,2 Many type II diabetics develop HT. This high prevalence is associated with increased stiffness of large arteries, which often precedes macrovascular events.…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension, obesity, and glucose intolerance (impaired glucose tolerance and noninsulin-dependent diabetes) are so commonly associated (1)(2)(3)(4)(5)(6)(7)(8)(9) as to suggest common pathogenetic mechanisms. Impaired glucose tolerance and obesity are characterized by hyperinsulinemia, which reflects peripheral insulin resistance.…”
Section: Introductionmentioning
confidence: 99%